PENGARUH PENDIDIKAN DAN LATIHAN, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PERUMAHAN KAWASAN PERMUKIMAN DAN PERTANAHAN PROVINSI SULAWESI SELATAN - Khaedir, Dzulkhair; Amin, Amelia Rezky (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
Human resource development is very necessary to be done in a planned and sustainable manner. In order for development to be implemented properly, it is necessary to set a development program based on scientific methods and based on the necessary skills. This study aims to find out and analyze the influence of education and training, competence and job satisfaction on the performance of employees of the Department of Housing, Settlements and Land of South Sulawesi Province and to know and analyze the variables that predominantly affect employee performance. The research has been conducted at the Office of Housing, Settlements and Land Of South Sulawesi Province. The analysis method used in this research is quantitative method, through regression testing by conducting validity and reliability test of the statement items of each variable as well as assumption test. The results showed that education and training have a significant positive influence on performance, this shows that the better education and training that employees participate in, the performance of employees in the Department of Housing, Settlements and Land of South Sulawesi Province will also increase. Competence has a significant positive influence on performance, this shows that the better the competence of employees will further improve the performance of employees in the office of the Department of Housing, Settlements and Land of South Sulawesi Province. Job satisfaction has a significant positive influence on performance, this shows that the higher the job satisfaction of employees of the Department of Housing, Settlements and Land of South Sulawesi Province, the better the performance will be. And the variable that has the dominant effect on employee performance is Job Satisfaction. Keywords: Education and Training, Competence, Job Satisfaction and Performance